Pomalidomide in myeloproliferative neoplasm-associated myelofibrosis - Schlenk, Richard Friedrich; Reiter, Andreas (Leukemia, 2017)
Myeloproliferative neoplasm (MPN)-associated myelofibrosis is a MPN characterized by bone marrow fibrosis, cytopenias, splenomegaly and constitutional symptoms. Pomalidomide, an immune-modifying drug, is reported to improve anaemia and thrombocytopenia in some patients with MPN-associated myelofibrosis. We designed a phase 2 study of pomalidomide in patients with MPN-associated myelofibrosis and anaemia and/or thrombocytopenia and/or neutropenia. Subjects received pomalidomide 2.0 mg/day in cohort 1 (n=38) or 0.5 mg/day in cohort 2 (n=58). Prednisolone was added if there was no response after 3 months in cohort 1 and based on up-front randomization in cohort 2 if there was no response at 3 or 6 months. Response rates were 39% (95% confidence interval (CI), 26-55%) in cohort 1 and 24% (95% CI, 15-37%) in cohort 2. In a multivariable logistic regression model pomalidomide at 2.0 mg/day (odds ratio (OR), 2.62; 95% CI, 1.00-6.87; P=0.05) and mutated TET2 (OR, 5.07; 95% CI, 1.16-22.17; P=0.03) were significantly associated with responses. Median duration of responses was 13.0 months (range 0.9-52.7). There was no significant difference in response rates or duration in subjects receiving or not receiving prednisolone. Clinical trial MPNSG 01-09 is registered at ClinicalTrials.gov (NCT00949364) and clinicaltrialsregister.eu (EudraCT Number: 2009-010738-23)
Gesehen am 11.05.2018
Advance online publication, 29 November 2016